Telecoupling cropland soil erosion with distant drivers within China. (15th June 2021) - Wang, Zhen; Zeng, Yi; Li, Cai; Yan, Hua; Yu, Shuxia; Wang, Ling; Shi, Zhihua
Abstract: Soil erosion on cropland is a result of the interaction between nature and human activities. The socioeconomic influencing factors of soil erosion have been less studied than the biophysical processes and previous studies have mainly focused on the impacts of local socioeconomic factors on soil erosion in the same region. However, since agricultural activities are densely connected to other socio-economic activities, the need for agricultural products from distant regions could potentially drive local soil erosion accompanying agricultural production. To the best of our knowledge, these telecoupling effects have not been studied. Here, we combined the Revised Universal Soil Loss Equation (RUSLE) and multiregional input-output analysis (MRIO) models to quantify the contribution of China's cross-provincial economic demand to local soil erosion at the provincial, sectoral, and supply chain levels. Our results show that a large amount of soil erosion in the southwest, northeast, and central regions is linked to the economic needs across provinces. Agriculture and food processing are the most important distant driving sectors. The driving effect of household consumption on soil erosion mainly occurs on shorter supply chains, while exports and capital formation drive soil erosion through longer chains. Our results indicate that local soil erosion management must consider the impact of distant agricultural product needs and coordinate food production and supply on a national scale to protect the ecological function of the land. Graphical abstract: Image 1 Highlights: Cropland soil erosion was linked to a multi-regional input-output table. 28.19% of cropland soil erosion was driven by distant final demand. Ten provinces had more than 1/4 of their soil erosion driven by other provinces' consumption. Agriculture, Food Processing, and Construction contributed 72.28% telecouped erosion. The telecoupled share increases along supply chains from 19.60% (tier 0) to 33.70% (tier 6).